Performance parameters for analytical method validation: Controversies and discrepancies among numerous guidelines - Raposo, Francisco; Ibelli-Bianco, Carolina (TrAC, Trends in analytical chemistry (Regular ed.), 2020)
The main objective of method validation process is to prove that an analytical method is acceptable for its intended purpose. The necessity for laboratories to use fully validated methods is now universally accepted as a way to obtain reliable results. There are diverse documents for method validation including information about different performance parameters. The classical performance characteristics are accuracy, limit of detection, precision, recovery, robustness, ruggedness, selectivity, specificity and trueness. Unfortunately, contradictory information is normally present among the method validation documents used by laboratories. The inconsistency about the performance parameters can generate some degree of confusion in the complete method validation process. This manuscript addresses controversial and discrepant information, focusing specifically on several national and international method validation guidelines published by prominent organizations and institutions which serve as guidance to validate new analytical methods by practitioners working in different fields. [Display omitted] •Analytical method validity depends on selected validation guideline.•In-depth assessment of performance parameters for method validation.•Evaluation of controversial and discrepant information.•Lack of common terminology for method validation.